Effect of Hook/Knitting Activities Against Decreased Stress Levels in Class II-A Medan Women's Laps - Maita Sarah (Science Midwifery, 2018)
Prison is a place where their environment can make stressful for prisoners. The environment always makes prisoners stress is uncontrolled prisoners behavior, undisciplinary, makes some fighting among prisoners, physically prisonable uncomfortable, narrow room due to overcapacity. Knitting activities were assumed to reduce stress levels for women prisoners. This research uses a quantitative method with quasy experiment approach. This research was collected in women prisons class II-a Medan. The population of this research were 535 respondents and samples obtained 84 respondents divided into two groups with each group of 42 respondents. Data analysis with univariate shows as frequency distribution of tables and bivariate analysis with independent sample t-tests. The results showed that 61.9% stress levels by intervention group was mild, and 38. 1% stress levels by intervention group was moderate. 52.4% stress levels by control group were severe, and 47.6% stress levels by intervention group was moderate. It was concluded that any influence between knitting activities towards decreasing stress levels with significant value (0,000 <0.05) and t-value (-8,015)> t-table (1,761). Recommendation for head of women prisons to provide knitting as a activity for reducing prisoners stress. Outcomes of the knitting activities can be sold in the public market. Recommendation for head of women prisons to provide knitting as a activity for reducing prisoners stress. Outcomes of the knitting activities can be sold in the public market. Recommendation for head of women prisons to provide knitting as a activity for reducing prisoners stress. Outcomes of the knitting activities can be sold in the public market.